Localization of dye degrading enzymes in Xanthomonas campestris MTCC 10, 108 - Shweta Sharma; Amir Khan; Ashok Munjal; Sanjay Gupta (Environment Conservation Journal, 2011)
Direct Red 28 is a carcinogenic direct diazo dye used for the coloration of paper products. It is recalcitrant and is mostly found in effluents of paper factories. Bacteria in consortia and monocultures those capable of decolorizing Direct Red 28 were isolated previously. The culture Xanthomonas campestris MTCC10, 108 was found able to decolorize dye consortia of Direct  Red 28, Amido Black, Reactive Black, Reactive Blue, Reactive Red concentration of 20 mg/l each, thus making final concentration approximately to 100 mg/l. It was observed that the rate of decolorization by Xanthomonas campestris MTCC10, was varied when incubated under optimum environmental conditions. Dye degradation occurred in the supernatant of sonicated cells, indicating that the dye degrading enzyme was located intracellularly. In present study the active component responsible for decolorization. Direct Red 28 was found as azoreductase rather than laccase and peroxidases enzymes. The optimum concentration of NADH was 0.10 mM and 250 μg of enzyme resulted reduction of 100 μg/ml (highest) Direct Red 28. Based on these results, the optimal enzyme assay conditions were 100μg/ml Direct Red 28, 0.1mM NADH and 250 μg/ml enzyme in 1 ml assay mixture.